Responsiveness and construct validity of two outcome measures of bilateral upper limb function in patients with chronic stroke - Tsai, Han-ting; Lau, Hiu-ying; Lin, Keh-chung; Li, Yi-chun; Lin, Chia-jung; Yao, Grace; Lee, Ya-yun; Chen, Wen-shiang; Chen, Chia-ling; Chang, Ya-ju; Horng, Yi-shiung (Frontiers in Neurology, 2024)
Background Stroke is a leading cause of long-term disability among stroke survivors. Despite the availability of numerous stroke rehabilitative therapies, such as mirror therapy, bilateral arm training, and robot-assisted therapy, the recovery of motor function after stroke remains incomplete. Bilateral arm function is a key component in stroke patients to perform activities of daily living and to reflect their functional autonomy. Objective This clinimetric study investigated and compared the construct validity and responsiveness of 2 bimanual activity outcome measures, the Chedoke Arm and Hand Activity Inventory (CAHAI) and the ABILHAND Questionnaire, in individuals receiving stroke rehabilitation. Methods The present study is a secondary analysis following the framework of the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). Individuals with chronic stroke (N = 113) were recruited from outpatient rehabilitation settings. Participants received 18 to 20 sessions of robot-assisted therapy, mirror therapy, combined therapy, or conventional rehabilitation for 4 to 6 weeks. The CAHAI, ABILHAND Questionnaire, and a comparison instrument, the Motor Activity Log (MAL), were administered twice at a 4- to 6-week interval to all participants. ABILHAND scores, in logits, were converted from raw ordinal scores into a linear measure. Results There was medium to large correlation of the CAHAI and the MAL (ρ = 0.60–0.62, p < 0.01) as well as the ABILHAND Questionnaire and the MAL (ρ = 0.44–0.51, p < 0.01). Change scores from the initial measurement to the post-intervention measurement demonstrated small to medium correlation of the CAHAI and the MAL (ρ = 0.27–0.31, p < 0.01) and medium to large correlation of the ABILHAND Questionnaire and the MAL (ρ = 0.37–0.41, p < 0.01). Overall, 7 of 8 hypotheses were supported. The hypothesis testing regarding the construct validity and responsiveness of the CAHAI and ABILHAND Questionnaire was confirmed. Conclusion The CAHAI and ABILHAND Questionnaire are both responsive and suitable to detect changes in bilateral arm functional daily activities in individuals with chronic stroke. Patient-reported outcome measures are recommended to use along with therapist-rated outcome measures for upper limb capacity evaluation in stroke rehabilitation. Further study with a prospective study design to capture specific clinical features of participants and the use of body-worn sensors, such as the arm accelerometer, is suggested.